Social Construction and Communication Pattern of Fishermen Community in South Java Sea Coast - Irzameingindra Putri Radjamin; Febriani, Maria Estherina ; Tanzil, Tjhan Silviana; Natalie, Abigel Chintya; Angelina, Nathania Veronica; Laurensia, Jessica Vania; Gabriela, Gracia (Journal of Economics, Business, and Government Challenges, 2024)
By considering the structure of environmental economic resources, which is the foundation for survival and as a social unit, a fishing community's sociocultural existence may be based on its reliance on the exploitation of marine and coastal resources. Having a very strong patron-client relationship structure, using optimal self-ability and adaptation, being competitive and achievement-oriented, appreciating skills and life success, being open and expressive, having a high level of social solidarity, having a system of division of labor, and engaging in consumptive behavior are the traits that make up the communication pattern of the fishing community. The purpose of this study is to identify and analyze social constructions and communication patterns in fishing communities living on the southern coast of Java. This study uses a qualitative approach with a literature study method. In Javanese society, sociologically, tradition has an important role in social action to identify its function and role at the same time in the group. The study's findings indicate that the social capital of the fishing communities along Java's southern coast, which includes social relations, social norms, respect, and trust, has an impact on the welfare and productivity of these communities. These communities are the center of organizing and preserving human capital with the fishermen's communication pattern, which is a process of exchanging ideas and meanings between individuals who communicate with each other.